Effect of FSW Heating Base Temperature on Tensile Strength and Hardness of AA 1100 Welds - Hadi, Syamsul; Setiawan, Agus; Nugroho, Pipit Wahyu; Hermansyah, Adi Dwi; Alfisahri, Anas Nur (Politeknik Negeri Ujung Pandang, 2020)
The research objective was to determine the effect of heating base temperature on tensile strength and hardness of AA 1100 welds in Friction Stir Welding (FSW). The research methodology includes preparing work pieces of size 150 mm x 100 mm x 3.6 mm from aluminium alloy AA1100 series, making work piece clamps that are suitable for the milling machine used, preparing heating plates 500 Watt for FSW, preparing tools from AISI-H13 material with a shoulder diameter of 20 mm and pin size of M5 x 3.4 mm for FSW, the implementation of FSW with a rotating speed of 1750 rpm and translation speed of 10 mm/minute, preparing hardness test specimens, preparing tensile test specimens refers to ASTM E8-13a, and data analysis of hardness test and tensile test results. The FSW results show that the hardness value increases with the increase in the width of the heating plate linearly for a temperature of 200oC from 10 mm to 30 mm which indicates better conditions, meanwhile decreases at a temperature of 175oC for heating plate width from 10 mm to 20 mm, but increases to 30 mm which is different for the temperature of 250oC and temperature of 300oC which have increased from 10 mm to 20 mm, but decreases towards 30 mm, and than the correlation between AA 1100 tensile strength and surface hardness of 3 heating plate widths is shown with the function of tensile strength, s (MPa) = -0.9699 x surface hardness (HV) + 102.01.